2020
DOI: 10.3390/app10041443
|View full text |Cite
|
Sign up to set email alerts
|

Parametric and Nonparametric PI Controller Tuning Method for Integrating Processes Based on Magnitude Optimum

Abstract: Integrating systems are frequently encountered in the oil industry (oil–water–gas separators, distillation columns), power plants, paper-production plants, polymerisation processes, and in storage tanks. Due to the non-self-regulating character of the processes, any disturbance can cause a drift of the process output signal. Therefore, efficient closed-loop control of such processes is required. There are many PI and PID controller tuning methods for integrating processes. However, it is hard to find one requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…As will be shown in Section 7, the method was also tested on a real process with present noise. Moreover, the proposed method for the PI controller [1] has also been tested on several processes with measurement noise. In all the mentioned tests, it was shown that the calculated areas and, therefore, the controller parameters, are not extensively sensitive on high-frequency process noise.…”
Section: Closed-loop Configuration and Magnitude Optimum Multiple Intmentioning
confidence: 99%
See 4 more Smart Citations
“…As will be shown in Section 7, the method was also tested on a real process with present noise. Moreover, the proposed method for the PI controller [1] has also been tested on several processes with measurement noise. In all the mentioned tests, it was shown that the calculated areas and, therefore, the controller parameters, are not extensively sensitive on high-frequency process noise.…”
Section: Closed-loop Configuration and Magnitude Optimum Multiple Intmentioning
confidence: 99%
“…Weighting factor b influences the disturbance-rejection and tracking performance. When b approaches 1, the integral gain K I (21) approaches 0 [1]. For b = 1, we obtained the following PID controller:…”
Section: Remarkmentioning
confidence: 99%
See 3 more Smart Citations